Integration of Electric Drive Systems in ICE to EV Conversion: A GT-Suite Approach - Setiawan, Yosua; Farid, Mohd (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
This study was focus on converting internal combustion engine (ICE) vehicles to electric vehicles (EVs) using GT-Suite simulations, focusing on the integration of electric drive system. With increasing global CO2 emissions, many nations aim to achieve carbon neutrality, making the shift to electrification crucial. While new battery electric vehicles (BEVs) produce significantly lower greenhouse gas (GHG) emissions, the high costs associated with new EV production remain a barrier to widespread adoption. Thus, converting existing ICE vehicles into EVs emerges as a more cost-effective and environmentally beneficial strategy. Using Toyota Avanza as a base model, replacing the ICE with a Synchronous AC motor and a LiFePO4 battery pack. Simulation results indicate competitive performance, with a 0-100 km/h acceleration time of 14 seconds, a top speed of 190 km/h, and an estimated driving range of 310 km. This study demonstrates that ICE-to-EV conversions can accelerate the transition to sustainable transportation.